2008
DOI: 10.1038/sj.bjc.6604734
|View full text |Cite
|
Sign up to set email alerts
|

Can ABCF2 protein expression predict the prognosis of uterine cancer?

Abstract: Uterine cervical and endometrial cancers are common malignant solid neoplasms for which there are no useful prognostic markers. In this study, we evaluate the relationship between ATP-binding cassette superfamily F2 (ABCF2) expression and clinical factors including clinical stage, histologic type, grade and prognosis in uterine cervical and endometrial cancer. Two hundred and sixty seven cervical and 103 endometrial cancers were studied. ATP-binding cassette superfamily F2 cytoplasmic expression was detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Previous studies have shown that ABCF2 expression correlates with cisplatin resistance in human bladder cancer T24 cell lines and clear cell ovarian cancer . ABCF2 was also indicated to be a potential marker for clear cell adenocarcinomas of the ovary and the uterine corpus . However, the precise molecular mechanism by which ABCF2 mediates cisplatin resistance is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ABCF2 expression correlates with cisplatin resistance in human bladder cancer T24 cell lines and clear cell ovarian cancer . ABCF2 was also indicated to be a potential marker for clear cell adenocarcinomas of the ovary and the uterine corpus . However, the precise molecular mechanism by which ABCF2 mediates cisplatin resistance is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…22 ABCF2 was also indicated to be a potential marker for clear cell adenocarcinomas of the ovary and the uterine corpus. 23,33 However, the precise molecular mechanism by which ABCF2 mediates cisplatin resistance is not clear. Our study provides evidence for a direct role of ABCF2 in mediating cisplatin resistance, since ABCF2 overexpression rendered A2780 cells more resistant to cisplatin and ABCF2 knockdown rendered resistant A2780 cells more sensitive to cisplatin ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Among three ABCF protein members, the expression level of ABCF2 is significantly higher in ovarian and cervical cancer cells but not in uterine endometrial cancer cells, thereby ABCF2 may serve as a prognostic indicator for ovarian and uterine cervical cancers 158,159 166 .…”
Section: Abcf Subfamilymentioning
confidence: 99%
“…Hence, ABCF2 was initially thought to be linked to drug resistance 157 . Among three ABCF protein members, the expression level of ABCF2 is significantly higher in ovarian and cervical cancer cells but not in uterine endometrial cancer cells, thereby ABCF2 may serve as a prognostic indicator for ovarian and uterine cervical cancers 158,159 . Additionally, ABCF2 possibly plays roles in mediating cisplatin‐induced drug resistance, evidenced by enhanced ABCF2 gene level in cisplatin‐resistant bladder cells and clear cell ovarian cancer 160–162 .…”
Section: Abc Transporter Subfamilies: Structure Function and The Rela...mentioning
confidence: 99%
“…TKIs in vitro [60][61][62] . Porém, apesar desse gene ser descrito com expressão alterada em diversos tipos de tumores, como câncer de mama 63 , câncer de útero 64 , cânceres de ovário 65,66 e câncer colo retal 67…”
Section: Mecanismos De Resistência Ao Tratamentounclassified